Coordinating abilities: recognition of a state of development of 11-13 years old boys - O.V. Ivashchenko; O.M. Khudolii; S.S. Iermakov; V.V. Prykhodko (H.S. Skovoroda Kharkov National Pedagogical University, 2018)
Purpose: To determine the possibility of recognizing the state of development of coordination abilities in boys 11-13 years old based on the methodology of multidimensional statistics. Materials: The study involved boys: 11 (n = 21), 12 (n = 20), 13 (n = 19) years. It was used 14 tests. Results: In the recognition of the state of development of coordination abilities in boys of 11-13 years old, the most important are the results in the tests: №2 "Standing long jump (cm)" (0.633); №12 "Rhythmic hand tapping" (-0.493); №15 "Tossing a ring over a peg" (-0.347). The enumerated tests characterize speed-power abilities, coordination of movements by hands and spatial precision of throws. In recognition of the state of development of coordination abilities in boys of 12-13 years old, the most important are the results in the tests: №12 "Rhythmic hand tapping" (0.691); №2 "Standing long jump (cm)" (0,387); №1 "30 m running (s)" (-0,356). The enumerated tests characterize the coordination of movements by the hands, speed-strength abilities and speed. Conclusions: Discriminant analysis allowed to determine: informative indicators for the walkthrough of the development of coordination abilities in boys of 11-13 years old; to answer such question as how significantly distinguished the state of development of coordination abilities in boys of 11-13 years old; which motor tests most significantly affect the differentiation of classes; to which class the object belongs to based on the values of discriminant variables.